The upregulation of tryptophan hydroxylase‐2 expression is important for premature ejaculation treatment with the selective serotonin reuptake inhibitor. (17th December 2021) - Zhu, Tianle; Gao, Pan; Gao, Jingjing; Liu, Xi; Jiang, Hui; Zhang, Xiansheng
Abstract: Background: Although there was some evidence to suggest that the serotonergic system in the brain played an important role in premature ejaculation (PE), tryptophan hydroxylase‐2 (TPH2) is considered to be the key enzyme for the synthesis of 5‐hydroxytryptamine (5‐HT) and few studies have reported that brain TPH2 is involved in the regulation of ejaculation. Objectives: This study aimed to investigate whether changes in brain TPH2 levels were associated with PE and to explore the effects of acute administration of dapoxetine on TPH2 expression in the brain of rats with rapid ejaculation. Materials and methods: Based on the ejaculation frequency, the male rats were split into three groups: "rapid, " "normal, " and "sluggish" ejaculators. The level of 5‐HT in the brain was determined by an enzyme‐linked immunosorbent assay. TPH2 expression was detected by western blot analysis and immunohistochemistry. Results: The results showed that the concentration of 5‐HT and the expression of TPH2 in rapid rats were the lowest, while those in sluggish rats were the highest. Correlation analysis also indicated the level of TPH2 was positively correlated with ejaculation latency ( r  = 0.8633, p  < 0.0001) and negatively correlated with ejaculation frequency ( r  = –0.874, p  < 0.001). In addition, dapoxetine acute administration to rapid rats resulted in upregulation of TPH2 expression in the brain. Discussion: There was an important link between the level of TPH2 and the change of ejaculation behaviors. Decreased expression of TPH2 in relevant brain regions will lead to rapid ejaculation. Moreover, the effect of dapoxetine on prolonging ejaculation may be due to the upregulation of TPH2 expression. Conclusion: We found the correlation between the level of TPH2 in the brain and PE. The findings in this study will open up a novel way for future research in PE therapy.